COMPUTER PROGRAMS FOR DESIGNING BUILDING STRUCTURES - Azamjonov Asadbek Tursunali o’g’li (Journals Park Publishing, 2023)
The article discusses in detail the possibilities of automating the process of processing projects and structural documents of buildings and construction structures, methods of design using modern computer technologies, computer design of construction structures, structural mechanics and construction structures.
Keywords: Construction Construction construction, finite elements, computing system, robustness, dynamics, geometric shape, vibration frequency, stagnation, deformation, ANSYS, COSMOS, PLAXIS dynamics, FLOWSTAR, SCAD, LIRA.